Pengaruh Mengkonsumsi Multiple Micro Nutrient (MMN) Terhadap Peningkatan Berat Badan Ibu Hamil - RD Rahayu (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: MMN, Weight. Pregnant women are one of the vulnerable groups may suffer from anemia because of events that occurred hemodelusi sat pregnancy. MMN is a supplement that contains multivitamins, iron and folate given to pregnant women as one of the Indonesian health ministry programs in an effort to prevent anemia during pregnancy. MMN order to determine the effect on weight gain for pregnant women. The research method to experiment with randomized. The population of 24 male mice. Twenty rats were given MMN. Data analysis using independent t-test. Results: Based on the average value MMN can increase weight gain. There is a difference in weight gain between before and after given MMN.